Donor Hepatic Occult Collagen Deposition Predisposes to Peritransplant Stress and Impacts Human Liver Transplantation. Issue 5 (30th August 2021) - Hirao, Hirofumi; Ito, Takahiro; Kadono, Kentaro; Kojima, Hidenobu; Naini, Bita V.; Nakamura, Kojiro; Kageyama, Shoichi; Busuttil, Ronald W.; Kupiec‐Weglinski, Jerzy W.; Kaldas, Fady M.
Abstract : Background and Aims: Environmentally triggered chronic liver inflammation can cause collagen deposits, whereas early stages of fibrosis without any specific symptoms could hardly be detectable. We hypothesized that some of the human donor grafts in clinical liver transplantation (LT) might possess unrecognizable fibrosis, affecting their susceptibility to LT‐induced stress and hepatocellular damage. This retrospective study aimed to assess the impact of occult hepatic fibrosis on clinical LT outcomes. Approach and Results: Human (194) donor liver biopsies were stained for collagen with Sirius red, and positive areas (Sirius red–positive area; SRA) were measured. The body mass index, aspartate aminotransferase/alanine aminotransferase ratio, diabetes score was calculated using 962 cases of the donor data at the procurement. LT outcomes, including ischemia‐reperfusion injury (IRI), early allograft dysfunction (EAD), and survival rates, were analyzed according to SRA and BARD scores. With the median SRA in 194 grafts of 9.4%, grafts were classified into low‐SRA (<15%; n = 140) and high‐SRA (≥15%; n = 54) groups. Grafts with high SRA suffered from higher rates of IRI and EAD ( P < 0.05) as compared to those with low SRA. Interestingly, high SRA was identified as an independent risk factor for EAD and positively correlated with the donor BARD score. When comparing low‐BARD (n = 692) with high‐BARD (n = 270) grafts in the same period, those with high BARD showed significantly higher post‐LT transaminase levels and higher rates of IRI and EAD. Conclusions: These findings from the largest clinical study cohort to date document the essential role of occult collagen deposition in donor livers on LT outcomes. High‐SRA and donor BARD scores correlated with an increased incidence of hepatic IRI and EAD in LT recipients. This study provides the rationale for in‐depth and prospective assessment of occult fibrosis for refined personalized LT management.